Ameliorative effect of liprotide-encapsulated vitamin D3 on blood glucose, calcium homeostasis, and vitamin D level in a vitamin D and calcium deficient rat model - Anjani, Gemala; Achmad Maulana, Reza; Putri, Sylvia Rahmi; Fulyani, Faizah; Syauqy, Ahmad; Afifah, Diana Nur; Ayustaningwarno, Fitriyono; Kusuma, Refani Alycia; Masruroh, Zulfatul (Frontiers in Nutrition, 2025)
Vitamin D3, recognized for its higher bioavailability and direct cell utilization, plays a vital role in the human body. Applying β-lactoglobulin with oleic acid (β-Lg-AO) as an encapsulating agent is anticipated to protect and enhance the transport of vitamin D3 to the gastrointestinal system. This study aimed to evaluate effect of liprotide-encapsulated vitamin D3 in a vitamin D-deficient rat on blood glucose, Vitamin D and calcium status. This is pre-post intervention. 24 mice were divided into 4 groups: (K-) normal rats; (K+) rat model of vitamin D and calcium deficiency; (P1) rat model of vitamin D and calcium deficiency with vitamin D3 intervention; (P2) rat model of vitamin D and calcium deficiency with liprotide-encapsulated vitamin D3 intervention. The administered dose of vitamin D3 was 180 IU (2 mL solution). Liprotide-encapsulated vitamin D3 intervention in vitamin D and calcium deficiency rats can significantly increase vitamin D (25 (OH)D) and calcium levels (p < 0.05). The increase in vitamin D (25 (OH)D) level was 53.69 ng/mL, and the increased calcium level was 4.38 mg/dL. Blood glucose levels of vitamin D-calcium deficiency rats decreased significantly (p < 0.05) by 39.87 mg/dL. Vitamin D3 encapsulated liprotide improves vitamin D and calcium in the blood more effectively than vitamin D3 without encapsulation in deficient rats.